Oral health status and its association with nutritional support in malnourished patients hospitalised in acute care. (7th July 2021) - Furuya, Junichi; Suzuki, Hiroyuki; Hidaka, Rena; Akatsuka, Ayano; Nakagawa, Kazuharu; Yoshimi, Kanako; Nakane, Ayako; Shimizu, Yukue; Saito, Keiko; Itsui, Yasuhiro; Tohara, Haruka; Sato, Yuji; et al.
Abstract: Objectives: This cross‐sectional study aimed to examine the oral health of malnourished acute‐care hospital inpatients, who were the subjects of a nutritional support team (NST). We also aimed to elucidate the systemic and nutritional factors associated with the oral health of those patients. Background: Interventions by NST are essential for inpatient nutrition management and require the active participation of dental professionals. However, information is limited regarding the state of oral health among acute‐stage malnourished inpatients. Materials and Methods: We enrolled 255 hospitalised patients (101 women, mean age: 69.7 ± 14.4 years) who were referred to an NST for nutrition management between April 2016 and July 2019. The main outcome was the Oral Health Assessment Tool (OHAT) scores. Moreover, we assessed participants' demographic characteristics, nutritional status, number of natural and functional teeth, posterior occlusal support, denture use, Dysphagia Severity Scale, whether oral health management was needed, and the methods of nutrition intake. Results: Several participants presented with a deteriorated oral health. Consequently, oral health management was often regarded necessary in these patients. Approximately half were fed by parenteral or tube feeding. Multiple regression analysis revealed the OHAT score has a positive association with age ( P = .008), and a negative association with body mass index ( P = .009) and the method of nutrition intake ( P = .028). Conclusion: Malnourished inpatients at an acute care hospital who were subject to an NST had a deteriorated oral health status. Additionally, poor oral health was associated with poor nutritional status and nutrition intake methods.